Self Esteem dan Tantangan Perawat di Ruang Isolasi Covid-19 - Rosnawati Rosnawati; Donny Tri Wahyudi; Sulidah Sulidah; Nurman Hidaya; Hasriana Hasriana (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
The care of Covid-19 patients with personal protective equipment is still a doubt not to contract the disease. This condition causes concern for nurses when going to carry out nursing care efforts in the Covid-19 isolation room. The purpose of the study was to explore nurses' self esteem experiences and challenges in caring for Covid-19 patients in the Covid-19 isolation room at RSUD dr. H. Jusuf SK. Qualitative research method with a phenomenological study approach. The research participants amounted to 10 nurses who had treated Covid-19. The results of this study indicate that the factors that affect nurses' self esteem when working in the Covid-19 isolation room are other people avoiding being placed in the isolation room. The conclusion of supporting factors is to work sincerely, want to give the best and be satisfied with the results of work as well as compliance with procedures and work motivation. It is hoped that increased support for facilities, incentives, praise can improve services more optimally.